Protected Esophago - Gastric Anastomosis: Lortat - Jacob's Technique - Balboa, Oscar; Voelker, Ricardo; Lerena, Ana (Cirugía del Uruguay, 1980)
Updating of Lortat -Jacob's esophago -gastric continent anastomosis consisting of complete invagination of esophagus in the stomach. Results obtained have been good.